Common and specific effects of TIE2 mutations causing venous malformations - Nätynki, Marjut (Hum Mol Genet, 2015)
Venous malformations (VMs) are localized defects in vascular morphogenesis frequently caused by mutations in the gene for the endothelial tyrosine kinase receptor TIE2. Here, we report the analysis of a comprehensive collection of 22 TIE2 mutations identified in patients with VM, either as single amino acid substitutions or as double-mutations on the same allele. Using endothelial cell (EC) cultures, mouse models and ultrastructural analysis of tissue biopsies from patients, we demonstrate common as well as mutation-specific cellular and molecular features, on the basis of which mutations cluster into categories that correlate with data from genetic studies. Comparisons of double-mutants with their constituent single-mutant forms identified the pathogenic contributions of individual changes, and their compound effects. We find that defective receptor trafficking and subcellular localization of different TIE2 mutant forms occur via a variety of mechanisms, resulting in attenuated response to ligand. We also demonstrate, for the first time, that TIE2 mutations cause chronic activation of the MAPK pathway resulting in loss of normal EC monolayer due to extracellular matrix (ECM) fibronectin deficiency and leading to upregulation of plasminogen/plasmin proteolytic pathway. Corresponding EC and ECM irregularities are observed in affected tissues from mouse models and patients. Importantly, an imbalance between plasminogen activators versus inhibitors would also account for high d-dimer levels, a major feature of unknown cause that distinguishes VMs from other vascular anomalies.